Prospecção e caracterização de peptídeos recombinantes miméticos a antígenos totais de herpesvírus bovino 1 por meio de phage display - Almeida, Greyciele Rodrigues de (2015)
Member of the Herpesviridae family, subfamily Alphaherpesvirinae, gender Varicellovirus, the bovine herpesvirus 1 (BoHV-1) has been associated with different clinical conditions (respiratory and genital/reproductive diseases) in cattle. There is no standard procedure to control or prevent infections caused by herpesviruses. In this sense, phage display was used to select new glycoprotein mimotopes antigen of BoHV-1 that has potential for use in vaccines and diagnostics. The phage display technique was performed using a linear random peptide library consisting of 12 amino acid residues fused to the protein III of M13 phage (no peptide) against BoHV-1 specific IgGs, purified by affinity chromatography. After three cycles of selection (biopanning) and amplification, 44 clones were isolated and their amino acid sequences were determined by sequencing generating 16 different sequences. ELISA, demonstrating the efficiency of selection from the specific antibodies, confirmed the reactivity of pooled clones. Another ELISA evaluated the individual specificity of the most frequent clones, the M13 phage was used as a negative control. We selected three peptides (B, C and E) with affinity for anti-BoHV-1 antibodies, and the E peptide (pepE), showed to have potential as antigen for antibody detection in a serological test for BoHV-1. Immunization of rabbits with the peptides induced specific production of serum antibodies, but they were not able do neutralize BoHV-1 cell lysis. The in silico analysis of the dodecapeptide E (1DRALYGPTVIDH12) enabled the identification of a new discontinuous epitope on the envelope glycoprotein B (gB Env) of bovine herpesvirus type 1 (BoHV-1). There is a short motif (338YKRD341) within a region of the env gB BoHV-1 with high similarity to motifs shared by dodecapeptide the N-terminal region (5YxARD1) of gB and HSV-1 (326YARD329), wherein the 328Arg residue is described as a target for neutralizing monoclonal antibodies (mAb) for HSV-1 gB. Besides the characterization of an antibody-binding site of the BoHV-1 Env gB, we have demonstrated that the phage-fused peptide has potential use as a reagent for virus diagnosis by phage-ELISA assay, discriminating BoHV-1 positive serum samples from negative ones.